Kebermanfaatan Media Sosial Bagi Generasi Internet : Studi Fenomenologi - Bambang Arianto (President University, 2023)
This study aims to elaborate information from the experiences of the internet generation in assessing the usefulness of social media. High dependence on social media has created benefits for the internet generation. This study involved five subjects of the internet generation who actively use social media in their daily activities. This research is a phenomenological type with an Interpretative Phenomenological Analysis method. Data were obtained through in-depth interviews with categories based on research subject statements. The research subject stated that the pattern of the internet generation in using social media in daily activities was known. The results of the study found that the internet generation assessed the usefulness of social media as a channel of information, interaction, participation, decentralization and accountability.